2020
DOI: 10.5713/ajas.18.0852
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid supplementation regulates key immunity-associated genes and pathways during the periparturient period in dairy cows

Abstract: Objective: The current research was aimed to profile the transcriptomic picture of the peripheral blood lymphocytes (PBLs) associated with immunity in Chinese Holsteins supplemented orally with coated folic acid during the periparturient period.Methods: The total of 123 perinatal cows were selected for this study and divided into three groups; group A (n = 41, 240 mg/500 kg cow/d), group B (n = 40, 120 mg/500 kg cow/d) and group C (n = 42, 0 mg/cow/d) based on the quantity of folic acid fed. Three samples of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 29 publications
2
35
0
Order By: Relevance
“…It has been noted that, during the periparturient period, the level of IFN-γ is significantly decreased [48]. Recently, our research team observed that folic acid treatment increases the level of IFN-γ and interleukin 17 (IL-17) [49], as shown in Figure 2. Changes in folic acid can alter the activity of methylenetetrahydrofolate reductase (MTHFR) and methionine synthase reductase (MTRR) genes, which have an essential role in chromosomal stability.…”
Section: Folic Acid Significantly Regulates Immunity In Periparturient Dairy Cattlementioning
confidence: 89%
See 2 more Smart Citations
“…It has been noted that, during the periparturient period, the level of IFN-γ is significantly decreased [48]. Recently, our research team observed that folic acid treatment increases the level of IFN-γ and interleukin 17 (IL-17) [49], as shown in Figure 2. Changes in folic acid can alter the activity of methylenetetrahydrofolate reductase (MTHFR) and methionine synthase reductase (MTRR) genes, which have an essential role in chromosomal stability.…”
Section: Folic Acid Significantly Regulates Immunity In Periparturient Dairy Cattlementioning
confidence: 89%
“…It has been noted that, during the periparturient period, the level of IFN-γ is significantly decreased [48]. Recently, our research team observed that folic acid treatment increases the level of IFN-γ and interleukin 17 (IL-17) [49], as shown in Figure 2.…”
Section: Folic Acid Significantly Regulates Immunity In Periparturient Dairy Cattlementioning
confidence: 89%
See 1 more Smart Citation
“…The extracted RNA was stored at −80°C and then was sent to the company (Annoroad Gene Technology Co., Ltd) for RNA sequencing. The details of RNA-seq analysis method used in this current study have been shown in our previous research (Muhammad et al, 2019).…”
Section: Extraction Of Rna and Sample Preparationmentioning
confidence: 99%
“…The suppression of IL-6 and IFN-γ usually occurs around parturition, which depresses immunity and exposes dairy cattle to mastitis [ 130 ]. Normal levels of IL-6 and IFN-γ are necessary for the maintenance of bovine immunity.…”
Section: Inhibitors Of the Jak-stat Pathway: Role In Mastitis And mentioning
confidence: 99%